Maternal cytomegalovirus immune status and hearing loss outcomes in congenital cytomegalovirus-infected offspring - Demmler-Harrison, Gail J. (PLoS One, 2020)
OBJECTIVES: The purpose of this study is to determine the relationship between maternal primary and recurrent CMV infection during pregnancy, symptoms at birth in the newborn, and long term hearing loss through18 years of age. PATIENTS AND METHODS: 237 mother-infant pairs in the Houston, Texas area identified through maternal CMV IgG and IgM antibody serologic screening and newborn screening using urine CMV culture to identify congenital CMV infection were enrolled in the Houston Congenital CMV Longitudinal Study. Mothers were categorized as having primary or recurrent or unknown maternal CMV infections, and newborns were categorized at birth as having symptomatic or asymptomatic congenital CMV infection, or as uninfected controls. All three newborn groups were followed longitudinally with serial hearing evaluations up to 18 years of age. The relationship between type of maternal CMV infection, newborn classification, and the occurrence of hearing loss over time was determined through Kaplan-Meier survival analysis, life table analysis, and a simulated ascertainment of maternal infection type for the unknown categories. RESULTS: Of 77 newborns with symptomatic congenital CMV infection, 12 (16%) of mothers had a primary CMV infection during pregnancy; 4 (5%) had a non-primary infection, and the type of infection in 48 (79%) could not be determined and were classified as unknown type of maternal infection. Fifty Seven (74%) of the 77 symptomatic children had hearing loss by 18 years of age, including 9 of the 12 (75%) who were born to mothers with primary infection and 48 (79%) of the 61 with unknown type of maternal infection. Of the 109 newborns with asymptomatic congenital CMV infection, 51 (47%) were born to mothers with a primary CMV infection during pregnancy, 18 (17%) to mothers with a recurrent infection; and 40 (37%) had unknown type of infection. Of these 109 asymptomatic cases, 22 (20%) developed hearing loss, including 14 out of 51 (28%) of those born to mothers with primary infection, two out of the 18 (11%) born to mothers with recurrent infection, and 6 out of the 40 (15%) to mothers of unknown infection type. Of the 51 uninfected newborn controls, 10 (20%) of mothers had a primary CMV infection during pregnancy, 5 (10%) had a non-primary infection, 10 (20%) were never infected, and 26 (51%) were assigned unknown type of infection. Three controls (6%) developed hearing loss, with 1 being born to a mother with primary infection and 1 to a mother never infected with CMV. CONCLUSIONS: Both primary and non-primary maternal CMV infections during pregnancy resulted in symptomatic and asymptomatic congenital CMV infection. Symptomatic congenital CMV infection was more likely to occur after primary maternal CMV infection. Sensorineural hearing loss occurred in children born to mothers with both primary and non-primary CMV infections, and in both asymptomatic and symptomatic congenital CMV infection, but was more common after maternal primary infection. Most, but not all, hearing loss in children with cCMV associated hearing loss was first detected within the first year of life.